Llewellyn's complete book of tarot : a comprehensive guide - Louis, Anthony, 1945- (Llewellyn Publications, 2016)
Discover basic reading techniques for a wide variety of systems, including Marseilles, Rider-Waite, and Thoth. Identify the meaning of associations, correspondences, reversals, and dignities, and experience the ways that tarot interacts with astrology and personal spirituality. Combine tarot reading with Kabbalah, numerology, Jungian psychology, journaling, and storytelling while exploring card selection, creativity, tarot ethics, and specialized spreads. Focusing on the use of tarot for insight, empowerment, self-understanding, and fortunetelling.